Population Pharmacokinetics of Trimethoprim-Sulfamethoxazole in Infants and Children - Autmizguine, Julie; Melloni, Chiara; Hornik, Christoph P.; Dallefeld, Samantha; Harper, Barrie; Yogev, Ram; Sullivan, Janice E.; Atz, Andrew M.; Al-Uzri, Amira; Mendley, Susan; Poindexter, Brenda; Mitchell, Jeff; et al. (Antimicrobial agents and chemotherapy, 2018)
Trimethoprim (TMP)-sulfamethoxazole (SMX) is used to treat various types of infections, including community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) and Pneumocystis jirovecii infections in children. Pharmacokinetic (PK) data for infants and children are limited, and the optimal dosing is not known. We performed a multicenter, prospective PK study of TMP-SMX in infants and children. Separate population PK models were developed for TMP and SMX administered by the enteral route using nonlinear mixed-effects modeling. Optimal dosing was determined on the basis of the matching adult TMP exposure and attainment of the surrogate pharmacodynamic (PD) target for efficacy, a free TMP concentration above the MIC over 50% of the dosing interval. Data for a total of 153 subjects (240 samples for PK analysis) with a median postnatal age of 8 years (range, 0.1 to 20 years) contributed to the analysis for both drugs. A one-compartment model with first-order absorption and elimination characterized the TMP and SMX PK data well. Weight was included in the base model for clearance (CL/ F ) and volume of distribution ( V / F ). Both TMP and SMX CL/ F increased with age. In addition, TMP and SMX CL/ F were inversely related to the serum creatinine and albumin concentrations, respectively. The exposure achieved in children after oral administration of TMP-SMX at 8/40 mg/kg of body weight/day divided into administration every 12 h matched the exposure achieved in adults after administration of TMP-SMX at 320/1,600 mg/day divided into administration every 12 h and achieved the PD target for bacteria with an MIC of 0.5 mg/liter in >90% of infants and children. The exposure achieved in children after oral administration of TMP-SMX at 12/60 and 15/75 mg/kg/day divided into administration every 12 h matched the exposure achieved in adults after administration of TMP-SMX at 640/3,200 mg/day divided into administration every 12 h in subjects 6 to <21 years and 0 to <6 years of age, respectively, and was optimal for bacteria with an MIC of up to 1 mg/liter.